Lysinibacillus sphaericus effect on fire affected soils and alnus acuminata sbsp. acuminata growth (2017)
"The Hacienda El Noviciado (Universidad de los Andes), located in Cota, Cundinamarca, Colombia, has been affected by a series of high intensity fires over the past 20 years caused by the interaction of different factors: littering, dry weather, temperature rise, dry season prolongation, water reservoirs and native plant cover loss, and invasive plantsï colonization (pyrogenic species), among others... This panorama presents great difficulties for the establishment of native plants, for these reasons, the aim of this study is to evaluate Lysinibacillus sphaericusï effect on the restoration of fire affected soils and Alnus acuminata sbsp. acuminata growth. A consortium formed by 7 L. sphaericus strains (OT4B.26, OT4B.31, OT4B.32, OT4B.49, CBAM5, III(3)7, 2362) was formulated to evaluate its effect on soil Nitrogen content and A. acuminata growth under greenhouse conditions." -- Tomado del Formato de Documento de Grado.